Prevalence of rheumatic heart disease in school children of urban Lahore. Issue 5 (24th October 2008) - Sadiq, M; Islam, K; Abid, R; Latif, F; Rehman, A U; Waheed, A; Azhar, M; Khan, J S
Abstract : Objective: To determine the prevalence of rheumatic heart disease (RHD) among school children in urban and semiurban areas of Lahore, Pakistan. Methods: A cross-sectional survey of school children aged 5–15 years from 70 schools of urban and semiurban Lahore was carried out by a team of cardiologists. Children were screened by clinical examination and diagnosis confirmed by echocardiography. Sociodemographic data were also collected. Results: Of 24 980 children screened, 986 (3.9%) had a confirmed cardiac lesion; 546 had RHD, 440 had congenital heart disease. The prevalence of RHD was 21.9/1000 children screened (95% CI 20.1 to 23.7). Their mean (SD) age was 10.7 (2.6) years and the female:male ratio was 1.6:1. Most (92.5%) were unaware of the diagnosis and less than 2% were taking rheumatic prophylaxis. All children belonged to a low socioeconomic group and 67% were undernourished. Conclusion: The prevalence of RHD in the urban school population of Lahore is among the highest in the world. The younger age of onset is a special feature and most are unaware of the diagnosis, and hence not receiving life-saving secondary prophylaxis.